In vitro intestinal simulation system on the carbon source utilization characteristics and mechanism of interspecific syntrophic effects of Bifidobacterium longum CECT7894 and Pediococcus pentosaceus CECT8330 - Li, Jinjun; Xu, Lei; Liao, Jiahao; Li, Xiaoqiong; Wang, Xin; Wu, Qinbin; Zhu, Liying (Frontiers in Pediatrics, 2023)
The combination of Bifidobacterium longum and Pediococcus pentosaceus is a clinically effective probiotic formulation for alleviating infantile colic; however, their utilization characteristics and mechanism of action surrounding their combined use of sugar sources remains unclear. Using in vitro simulation technology, this study set up individual and mixed cultures of the two probiotics at unique concentrations, and different types of prebiotics, carbohydrates and polyols were added. Gas and short-chain fatty acid production, substrate utilization, as well as growth of the individual and mixed probiotics were detected at the beginning of fermentation, 24 h, and 48 h. Further, the mechanism of the syntrophic effect of the two 2 probiotics was explored based on their growth characteristics. It was found that neither strain produced gas after 24 h and 48 h of cultivation, but could synergistically utilize fructo oligosaccharides (FOS) when mixed.There was an increasing trend of acetic acid production for B. longum in yeast extract, casitone and fatty acid (YCFA) and FOS medium with increasing of bacterial concentrations at 24 h and 48 h; whereas the trend for P. pentosaceus was less obvious. When bacterial concentrations were > 5 billion CFU•g-1, the mixed culture showed significantly lower acetic acid production than B. longum alone. By adding lactic and acetic acids to the YCFA medium and observing P. pentosaceus growth, the results suggested that Pediococcus pentosaceus could use the acetic acid and lactic acid produced by Bifidobacterium longum for growth. When the bacterial concentration was 5 billion CFU•g-1, the acetic acid production of B. longum was significantly higher in the mixed cultures in lactulose, lactose, FOS, galactooligosaccharide, and inulin medium; whereas the reverse was true for culturing in xylitol, carboxymethyl cellulose sodium, and sorbitol medium. Further, the mixed cultures produced significantly more acetic acid than B. longum alone. In summary, through in vitro simulation experiments, the optimal ratio and potential interaction mechanisms between B. longum and P. pentosaceus were revealed here, offers a basis for understanding how the probiotic combinations may improve infant colic symptoms by influencing the gut pH and regulating the gut microbiota mechanisms.